Mapping vulnerability: Opportunities and limitations of participatory community mapping. (April 2019) - Sullivan-Wiley, Kira A.; Short Gianotti, Anne G.; Casellas Connors, John P.
Highlights: Smallholders are increasingly vulnerable to multi-hazard environments. Land management for risk reduction is under-represented in vulnerability maps. A grounded approach illuminates socially-mediated perceptions and management. Participatory mapping can add nuance to discussions of vulnerability, but not alone.